2023
DOI: 10.1021/acs.chemrev.2c00659
|View full text |Cite
|
Sign up to set email alerts
|

When Phased without Water: Biophysics of Cellular Desiccation, from Biomolecules to Condensates

Abstract: The molecular machinery that enables life has evolved in water, yet many of the organisms around us are able to survive even extreme desiccation. Especially remarkable are single-cell and sedentary organisms that rely on specialized biomolecular machinery to survive in environments that are routinely subjected to a near-complete lack of water. In this review, we zoom in on the molecular level of what is happening in the cellular environment under water stress. We cover the various mechanisms by which biochemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 320 publications
(575 reference statements)
0
22
0
Order By: Relevance
“…An emerging paradigm in the anhydrobiosis field is the prevalent enrichment of IDPs that help to mediate protection during drying (Hand et al, 2011; Hesgrove & Boothby, 2020; Romero‐Perez et al, 2023). Transient helicity, and the acquisition of increased helical content during desolvation, has been reported in many desiccation‐related IDPs spanning diverse families (Bremer et al, 2017; Shimizu et al, 2010; Tunnacliffe et al, 2010; Yamaguchi et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An emerging paradigm in the anhydrobiosis field is the prevalent enrichment of IDPs that help to mediate protection during drying (Hand et al, 2011; Hesgrove & Boothby, 2020; Romero‐Perez et al, 2023). Transient helicity, and the acquisition of increased helical content during desolvation, has been reported in many desiccation‐related IDPs spanning diverse families (Bremer et al, 2017; Shimizu et al, 2010; Tunnacliffe et al, 2010; Yamaguchi et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…An emerging paradigm in the anhydrobiosis field is the involvement of intrinsically disordered proteins (IDPs) in mediating desiccation tolerance (Boothby et al, 2017; Boothby & Pielak, 2017; Romero‐Perez et al, 2023; Tunnacliffe et al, 2010; Yamaguchi et al, 2012). Some of the first IDPs implicated in anhydrobiosis were late embryogenesis abundant (LEA) proteins, which were first identified in cotton seeds (Dure et al, 1981), but have subsequently been found in a number of diverse organisms (Battista et al, 2001; Browne et al, 2002; Dure et al, 1981; Hand et al, 2011; Kikawada et al, 2006; Schokraie et al, 2010; Tunnacliffe et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Under dehydrating conditions, water molecules evaporate, and solute concentrations increase, challenging protein stability. , The contact of proteins with the air–water interface also increases. Proteins tend to adsorb and denature at the interface, to an extent comparable to their accumulation at water–oil interfaces (Figure ).…”
Section: Introductionmentioning
confidence: 99%
“…Glassy matrices also protect DNA and lipids, and similar strategies are employed in protection from other types of stress, including freezing. These aspects are not covered here, but excellent reviews are available. ,,, …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation